NUTRITIONAL STATUS INTAKE ON FRUITS AND VEGETABLES AMONG ASNAF STUDENTS IN UiTM PERLIS - Jamil Ahmad, Siti Nur Ainie; Azhar, Nur Fatini Izzati; Jamaludin, Masshera; Mohd Rosli, Norfaezah; Ismail, Zulkifli; Hj Ismail, Ahmad Dzulkarnain (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Insufficient consumption of fruits and vegetables has been associated with millions of deaths annually, contributing to conditions such as heart disease and cancer. In the context of Malaysia, this issue is particularly prevalent. The NHMS 2023 reports that 95.1% of adults do not consume the recommended daily servings of fruits and vegetables, averaging only two servings per day instead of the advised five. This problem extends across both rural and urban areas, with urban regions also exhibiting high rates of obesity and poor dietary habits. To better understand and address this concern, a study was conducted involving asnaf (economically disadvantaged) students at Universiti Teknologi MARA (UiTM) Perlis. Using a random sampling method, 217 students participated by maintaining daily food diaries in both English and Malay. These diaries were analyzed using MyFitnessPal to assess nutrient intake accurately. The findings were alarming. On average, students failed to meet the minimum recommended levels for essential nutrients such as vitamin A, C, iron, potassium, and fiber. For instance, the average daily intake included just 5.4 µg of vitamin A and 3.3 grams of fiber, significantly under the level required for good health. In conclusion, many asnaf students at UiTM Perlis do not consume adequate amounts of fruits and vegetables, placing them at increased risk for long-term health issues. This situation demonstrates the need for more awareness and support for healthy eating, particularly among vulnerable student populations.